2014
DOI: 10.3233/jad-140696
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetes Mellitus and Mild Cognitive Impairment in Middle-Aged Men and Women

Abstract: Our data show that T2DM is associated with MCI and MCI subtypes in middle-aged, but not in old-aged participants. Furthermore, the results indicate a gender-specific vulnerability of T2DM on cognition, especially in MCI subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 0 publications
4
24
1
2
Order By: Relevance
“…The association between T2DM and AD was not observed in one study with very old T2DM subjects (≥80 years old) (48). The association between T2DM and AD was probably specific with the age at onset of T2DM as the same relationship was observed between the age at onset of T2DM and MCI (72). Although the cortical atrophy in T2DM was reported to resemble the pattern as in preclinical AD [19], the presence of T2DM does not affect amyloid and neurofibrillary tangle burden in a sample of clinically and pathologically confirmed AD cases [84].…”
Section: T2dm As a Risk Factor For Admentioning
confidence: 56%
See 2 more Smart Citations
“…The association between T2DM and AD was not observed in one study with very old T2DM subjects (≥80 years old) (48). The association between T2DM and AD was probably specific with the age at onset of T2DM as the same relationship was observed between the age at onset of T2DM and MCI (72). Although the cortical atrophy in T2DM was reported to resemble the pattern as in preclinical AD [19], the presence of T2DM does not affect amyloid and neurofibrillary tangle burden in a sample of clinically and pathologically confirmed AD cases [84].…”
Section: T2dm As a Risk Factor For Admentioning
confidence: 56%
“…Older age (>75 years) and long duration of diabetes are major risk factors for converting MCI to dementia, while the use of oral hypoglycemic agents or statins was associated with a significantly reduced risk for converting MCI to dementia [74]. T2DM has been found to be associated with MCI or MCI subtypes in middle-aged (50-65 years old) subjects but not in elderly individuals (66-80 years old) [72]. However, T2DM was shown to be associated with an increased risk of MCI in an elderly group of subjects (70 years and older) in another study [75].…”
Section: T2dm and MCImentioning
confidence: 99%
See 1 more Smart Citation
“…The following definitions were used for exclusion of participants based on cognitive impairment, clinically relevant depressive symptoms, and dementia. Cognitive impairment at t1 was defined as a performance of one standard deviation (SD) below the age‐ and education‐adjusted mean except for the clock‐drawing test, where a performance ≥3 was rated as impaired (for a detailed description, see the study by Winkler et al [15]). A Center for Epidemiologic Studies Depression scale score of ≥18 was defined as clinically relevant depressive symptoms (CES‐D, see 2.5 [16]).…”
Section: Methodsmentioning
confidence: 99%
“…Literature suggests there is a correlation between type 2 diabetes and mood alterations such as depression and neuropsychiatric disorders; for instance, major depressive disorder 10, 11 , schizophrenia 12, 13 , mild cognitive impairment 14, 15 and suicidal behavior 16 . It also has been observed that depression could cause an increase in all-cause mortality risk (approximately 70%) 17 ; it is also the most common mental disorder and generates a great impact on people and society in terms of suffering, disability and economic costs, a phenomenon that seems to occur in many parts of the world; in this context, it has been reported that depression affects 350 million people worldwide 18 ; for example, a research by Talbot et al suggests that depression is not only a direct consequence of diabetes; depression may also be a risk factor for the onset of diabetes type 2 19 .…”
Section: Introductionmentioning
confidence: 99%